THE INFLUENCE OF POLITICAL EDUCATION ON POLITICAL PARTICIPATION AWARENESS AMONG PEOPLE WITH DISABILITIES - Edy Sijaya; Mohammad Ahmad Bani Amer; Suhana Sarkawi (Adisam Publisher, 2025)
This study examines the influence of political education on political participation awareness among people with disabilities in Indonesia. Inclusive political education is believed to be able to improve the understanding of people with disabilities regarding their political rights, the electoral process, and the importance of active involvement in democratic life. Through a descriptive qualitative approach and literature review, this study found that political education delivered through various methods, such as socialisation, lectures, and accessible materials, can increase knowledge, self-confidence, and motivation among people with disabilities to participate in elections and other political activities. However, there are still challenges in the form of limited facilities, materials that are not fully accessible, and social and psychological barriers. Therefore, an integrated strategy involving the government, election organisers, disability organisations, and the wider community is needed to ensure that political education is accessible in a fair and sustainable manner, so that the political participation of persons with disabilities can increase in both quantity and quality.